Intrapreneurship practices in local government to improve service delivery - Ntoyanto-Tyatyantsi, N.; Ceki, B. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
Local government is facing service delivery challenges; this demands application of intrapreneurship practices. This study investigated the intrapreneurship practices at local government and recommended practices to improve efficiency in service delivery at local government level. The research is situated within the interpretivist paradigm and employed the qualitative method. In-depth, semi-structured interviews were conducted with managers of the O.R. Tambo Municipalities. Data was analysed through content analysis. Municipality documents were also used for triangulation purposes. Results revealed that intrapreneurship practices are not present at municipality due to several factors. This study recommends intrapreneurship practices that could be adopted by municipalities in order to foster innovation and enhance the efficient and effective delivery of services. The findings of this study may be extended to other government institutions.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Innovation; Intrapreneurship; Service delivery; Resources; Reward; Business practices; Local government